37 Cardiovascular Effects of Unilateral Nephrectomy in Human Kidney Donors. (6th June 2015) - Moody, William; Ferro, Charles; Edwards, Nicola; Chue, Colin; Lin, Erica; Cockwell, Paul; Steeds, Richard; Townend, Jonathan; Taylor, Robin
Abstract : Introduction: There is a graded association between chronic kidney disease and cardiovascular (CV) risk but proof of causality is lacking and the pathophysiological mechanisms responsible for this relationship remain unclear. We hypothesised that the reduction in glomerular filtration rate (GFR) accompanying nephrectomy in live kidney donors causes increased left ventricular (LV) mass, impaired LV function and increased aortic stiffness. Methods: This was a multicentre, parallel group, blinded end point study of live kidney donors and healthy controls (n = 124). The primary outcome was change in LV mass assessed by MRI (baseline to 12 months). Pre-specified secondary outcomes included changes in: isotopic GFR; LV strain; blood pressure (BP); aortic pulse wave velocity (PWV) and distensibility; and cardiac biomarkers. Results: When compared to controls, LV mass (+7 +/- 10 g vs. −3 +/- 8 g; P < 0.001), LV mass-volume ratio (+0.06 +/- 0.12 g/ml vs. −0.01 +/- 0.09 g/ml; P < 0.01) and PWV (+0.5 +/- 0.9 m/s vs. −0.1 +/- 0.7 m/s; P < 0.001) were increased in donors. Aortic distensibility (−0.29 +/- 1.38 × 10 –3 mmHg -1 vs. +0.28 +/- 0.79 × 10 –3 mmHg -1 ; P = 0.03) and global circumferential strain (−1.1 +/- 3.8% vs. +0.4 +/- 2.4%; P = 0.04) were reduced in donors. The decrease in GFR (−30 +/- 12 mL/min/1.73 m 2 ) in donors was accompanied by increases in uric acid (+56 +/- 35 micromol/L vs. +2 +/- 33 micromol/L; P < 0.001), parathyroid hormone (+1.1 +/- 1.6 pg/mL vs. +0.4 +/- 1.3 pg/mL; P = 0.03) and hs-CRP (+1.7 +/- 5.3 mg/dl vs. -0.7 +/- 5.2 mg/dL; P < 0.01), with greater risks of developing detectable hs-Troponin T (21% vs. 2%; OR 16.2; P < 0.01) and microalbuminuria (7% vs. 0%; OR 3.74; P = 0.04). There were no significant changes in circulating levels of renin or aldosterone and no changes in brachial or central BP. Change in GFR was an independent predictor of the change in LV mass after adjustment for age, sex, baseline LV mass, and 12-month changes in BP, uric acid and parathyroid hormone (Beta = −0.3, R 2 = 0.31, P = 0.002). Conclusions: A modest reduction in GFR causes increased LV mass, LV systolic dysfunction, increased aortic stiffness and adverse changes to CV biomarkers. Reduced GFR should be regarded as an independent causative CV risk factor.